Improving the Accuracy of the Calibration Method for Structured Light System - Nguyen, Thi Kim Cuc; Nguyen, Van Vinh; Nguyen, Thanh Hung; Nguyen, Viet Kien (Old Journal, 2018)
In a structured light system, calibration is an important step for estimating the intrinsic and extrinsic parameters of the camera and projector. System calibration errors directly affect the measurement errors. Therefore, the accurate calibration is the main prerequisite for a successful and accurate surface reconstruction. In this paper, the effect of checker size and checkerboard angle on the accurate calibration for a structured light system is presented. Relations between calibration error and checker size, fitting plane error and checkerboard angle are also studied. The purpose of the research is to achieve high accuracy when calibrating the system, by selecting the optimum checker size and determining the limited checkerboard angle Δβ in the whole volume of measurement 200(H)×250(W)×100(D)mm³